CCPB a system for filtered news hoarding and automatic private publishing:CCPB a device for the marketplace of attention - Marques, Artur (2018)
We live in a "marketplace of attention" constantly facing the truism of "a wealth of information creates a poverty of attention". Many people are increasingly aware of a growing number of worthy-of-their-time content sources, happenings, events, etc., but it is not only becoming harder to consume them all, but also selecting in itself has reached a level of complexity that may cause frustration. "CCPB" (Consumer, Capturer, Publisher Bot) is a work-in-progress system that enables users to automatically capture configurable content from WWW sources (e.g. nytimes.com, wsj.com, ft.com, etc.) and have it privately published for later reading. Publication is done in a private local blog. Once captured, the content can be consumed and searched offline. Some common paywall systems might be automatically defeated by the bot's consumption algorithms. The user can configure what to accept and what to reject via regular expressions.CCPB works as personal device for the "marketplace of attention", running on behalf of its user, always harvesting and publishing what's new, for asynchronous consumption, regardless of online availability.